Al-‘Alaqah bayna Isti‘āb al-Mufradāt fī Muṣṭalaḥāt al-‘Arabiyyah wa Kafā’ah al-Khiṭābah al-‘Arabiyyah bi-Jam‘iyyat al-Khuṭabā’ bi-Ma‘had Darussalam Gontor, Ponorogo: The Relationship Between Vocabulary Comprehension In Arabic Rhetoric Terminology and Arabic Rhetoric Proficiency at the Association Of Orators at Darussalam Gontor Modern Islamic Institution, Ponorogo - Ahmad Farhan Rif’an Najib; Hamzah Auzai Aulia Fasha; Deri Rizqi Rivanto (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to explore the relationship between vocabulary mastery in Arabic rhetoric terms and the speech proficiency of members of Jamiyyatu-l-Khuthaba' at Pondok Modern Darussalam Gontor. Arabic rhetoric requires strong vocabulary mastery to facilitate the effective delivery of ideas, thereby enhancing speech proficiency. This research employs a descriptive quantitative approach with a correlation method. Data were collected through observation, written tests to measure vocabulary mastery, and oral tests to assess speech proficiency. Data analysis was conducted using the product-moment correlation technique at a 5% significance level. The results showed that the average vocabulary mastery score was 33.7, while the average speech proficiency score was 33.8, both at an adequate level. The correlation coefficient between vocabulary mastery and speech proficiency was found to be very high, at 0.935. This indicates that vocabulary mastery has a significant relationship with speech proficiency. Based on these findings, it is recommended that the management of Jamiyyatu-l-Khuthaba' enhance vocabulary training, provide exemplary speeches, and encourage members to recognize the importance of vocabulary in improving their speech competencies. Keywords: Arabic Rhetoric, Correlation Analysis, Jamiyyatu-l-Khuthaba', Speech Proficiency, Vocabulary Mastery.